THE EFFECT OF GREEN PRODUCT, HALAL LABEL AND SAFI COSMETIC BRAND IMAGE ON PURCHASE DECISIONS MODERATED BY WORD OF MOUTH IN THE MUSLIM COMMUNITY OF PALEMBANG CITY - Karinta Fakhira; Mismiwati Mismiwati; Fernando Africano; Riduwansah Riduwansah; Oki Sania Riski (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2022)
This research was on to find out the influence of green products, halal labels, the brand image of Safi Cosmetics, and word of mouth as moderators to wards purchasing decisions of the Muslim consumers in Palembang. The sample used in this research was the Muslim consumers in Palembang with purposive sampling techniques. The number of samples in this study was 90 samples obtained from the questionnaire. The research used the quantitative approach with Moderated Regression Analysis assisted by SPSS 21. The results reveal that green product has no effect on purchasing decisions, the halal label has a positive effect on purchasing decisions, brand image has a positive effect on purchasing decisions, word of mouth has a positive effect on purchasing decisions, and word of mouth weakens the relationship between green products and purchasing decisions. Â